Методи виявлення атак на систему навігації БПЛА. Частина 2 - Головко, М. А. (ХНУРЕ, 2024)
This paper discusses the implementation of methods for protecting un manned aerial vehicles from global positioning system spoofing attacks. A new self-diagnosis method is proposed, which allows the UAV to independently assess the presence of changes in its subsystems and identify signs of a cyberattack.
Keywords: навігація БПЛА; атака на систему навігації